(untitled) (Raparin Journal of Humanities (RJH), 2021)
This researched has tried to analyze the philosophy of pragmatics and its development as well as applying it on the level of America’s foreign policy in the cabinet of both American Presidents Barack Obama and Donald Trump in a comparative way to analyze and investigate it. The philosophy of Pragmatics in the center of American policy had an important position in the formulation of foreign policies and decisions and its application between Barack Obama and Donald Trump’s administration, was embodied in different forms and mechanisms which understanding this political perspective and direction is helpful to increase an understanding about formulation and application of American foreign policy. It has been tried to answer the main question of the research within the context of this research, which is how did the main and clear difference of getting benefit from pragmatism between both Obama and Trump’s administration has reflected in the American foreign policy? In the research, it was hypothesized that pragmatism was generally used in American foreign policy to protect America’s living interests and applying pragmatism between each Obama and Trump’s administration and how it is reflected in American foreign policy. This research has reached the conclusion that pragmatism in the era of Barak Obama’s administration has embodied itself in the form of a clever and hidden soft Power that has not ignored actors and other parties in the international arena despite the desire to protect American interests. But in Donald Trump’s era, pragmatism has applied itself in the form of hard, obvious pragmatism, economic, and political interests of America, which was the main desire to protect America’s interests.